NILAI DAN PRINSIP ISLAM TERHADAP PENDAPATAN MASYARAKAT KECAMATAN SEMAMPIR SURABAYA - Cholid Imami; Raditya Sukmana (Universitas Airlangga, 2019)
This research is a quantitative research using Anova One-way technical. The findings of this study indicate that people who in their lives apply Islamic values (Self Responsibility and Community Responsibility) in their lives will have higher incomes than people who do not apply Islamic values, these findings are in harmony with what was written by Ali Djalali (1993) poverty is the responsibility of each individual, therefore the understanding in applying the value of Islam should be known to the public to get out of the vicious cycle of poverty. Future research is suggested that the Government's policy to be added in the measurement indicator because in Islamic values also includes the responsibility of the government.Keywords: Self Responsibility, Community Responsibility, Islamic Values, Islamic Ethics, PovertyREFFERENCESAl-Qur’an dan terjemahannya. 2000. Kementrian Agama Republik Indonesia.Senadjki, Abdul. 20014. .An empical study on the influence of Islamic values in poverty alleviation. Malasyia: Universiti Tunku Abdul RahmanAhmad, K. 1981.Islam, Poeverty and Income Distribution,The Islamic Foundation, Leicester.Akhtar, M.R. (2000), “Poverty alleviation on a sustainable basis in the Islamic framework”, The Pakistan Development Review, Vol. 39 No. 4, Part II, pp. 631-647.Ali Aldalaji, A. (1993), Poverty and the Poor,Dar Al-kotob Al-ilmiyah, Beirut.Chapra, M.U. (1991), “The need for a new economic system”, Review of Islamic Economics, Vol. 1 No. 1, pp. 9-47.Chapra, M.U. (1992), Islam and the Economic Challenge, Islamic Foundation, Leicester.Chapra, M.U. (1993), Islam and Economic Development, International Institute of Islamic Thought and Islamic, Research Institute, Islamabad.Choudhury, M.A. (1983), “Principles of Islamic economics”, Middle Eastern Studies, Vol. 19 No. 1,pp. 93-103.Farooq, M.O. (2008), “The challenge of poverty and poverty of Islamic economies”, Journal of Islamic Economies, Banking and Finance, Vol. 4 No. 2, pp. 35-58.Hasibuan, S. (2010), “Poverty alleviation: an Islamic way”, paper presented at the Seventh International Conference – The Tawhidi Epistemology: Zakat and Waqf Economy, Bangi.Kahf, M. (1991), “The economic role of the state in Islam”, Lecture presented at the seminar on Islamic Economics, Dacca.Khan, F. (2010), “WAQF: an Islamic instrument of poverty alleviation – Bangladesh perspective”, paper presented at the Seventh International Conference – The Tawhidi Epistemology: Zakat and Waqf Economy, Bangi.Khan, M.F. (1995), Essays in Islamic Economics, Islamic Foundation, Leicester.Khan, M.S. and Abbas, M. (1992), “Islam and the economic system”, Review of Islamic Economics, Vol. 2 No. 1, pp. 1-29.Khan, W.M. (1985), Towards An Interest Free Islamic Economic System, Islamic Foundation, Leicester.Krejcie, R.V. and Morgan, D.W. (1970), “Determining sample size for research activities”, Educational and Psychological Measurement, Vol. 30 No. 1, pp. 607-610.Liala, T. (2010), “Islamic microfinance for alleviating poverty and sustaining peace”, Paper presented at the World Universities Congress, Canakkale, 20-24 October.Miaoulis, G. and Michener, R.D. (1976), An Introduction to Sampling, Kendall/Hunt Publishing Company, Dubuque, Iowa.Rahman, M.M. (2010), “Islamic micro- finance programme and its impact on rural poverty alleviation”, Banking, Vol. 7 No. 1.Sadeq, A.M. (1997), “Poverty alleviation: an Islamic perspective”, Humanomics, Vol. 13 No. 3, pp. 110-134.Sekaran, U. (2009), Research Methods for Business, John Wiley&Sons, New-Delhi.Sen, A. (1981), Poverty and Famines: An Essay on Entitlement and Deprivation, Clarendon Press, Oxford.Shahata, S. (1984), “Some of the concepts and principals in the Islamic economics”, Journal of Islamic Banks, Vol. 39 No. 1.Siddiqi, M.N. (1996), Role of the State in the Economy: An Islamic Perspective, Islamic Foundation, Leicester.Sirageldin, I. (2000), “Elimination of poverty: challenges and Islamic strategies”, Islamic Economic Studies, Vol. 8 No. 1, pp. 1-16.Subaramaniam, K. (2011), Exploring the Problem of Gambling and Loan Sharks in Malaysia: A Case Study Approach, Universiti Tunku Abdul Rahman, Kampar.Yusri, A. (2015), The Economic and Social Development in Islam, Youth Foundation University, Alexandria.Zaman, A. (2010), “Islamic economics: a survey of the literature”, Islamic Studies, pp. 37-63.